Strategi Komunikasi dalam Industri Pariwisata Pasca Pandemi Covid-19 - Ita Suryani; Asriyani Sagiyanto; Intan Leliana (LPPM Universitas Bina Sarana Informatika, 2022)
In Indonesia, the tourism sector is better known to the world because it has many tourist destinations spread across the country. Natural aesthetics and customs are an attraction for tourists to visit Indonesia. Since the announcement of the Covid-19 pandemic as a national disaster, forcing governments around the world to take policies and actions to temporarily stop activities by implementing Lockdown. The implementation of the lockdown has greatly impacted various sectors, both the economic, social and tourism sectors. Entering the new normal era, the Indonesian government provides the tourism sector with the flexibility to recover by operating again in accordance with the implementation of health protocols. The purpose of this study is to find out how the communication management strategy is carried out by the Ministry of Tourism and Creative Economy/Tourism and Creative Economy Agency of the Republic of Indonesia to restore the tourism sector after the pandemic. The method used in this research, namely the case study method, is a research method that uses different data sources that can be used to comprehensively explain various aspects of an individual, group, program, organization or event systematically. The conclusion shows that the post-pandemic communication management strategy is carried out with a centralized internal and external communication strategy by determining a spokesperson, improving the quality of human resources, creating a special channel for pandemic information on the internet site, providing the latest information regularly to the company's crisis team, submitting related policies/SOPs. handling pandemics, conducting virtual activities with related divisions. Keywords: Communications Strategi, Communication Tourism, Tourist Destination, Pandemic Covid-19